Emerging precision therapies for gastric cancer. Issue 4 (3rd July 2020) - Cartwright, Elizabeth; Athauda, Avani; Chau, Ian
ABSTRACT: Introduction: Gastric cancer (GC) is a leading cause of cancer-related death and a significant global health burden. Chemotherapy remains the mainstay of treatment in advanced disease and only trastuzumab in combination with upfront fluoropyrimidine/platinum chemotherapy for human epidermal growth factor receptor 2 (HER2) positive disease and ramucirumab together with paclitaxel in the second line have demonstrated a significant survival benefit over chemotherapy alone. Despite the focus on a molecularly targeted approach, treatment gains have been modest and GC remains an area of great unmet need. Areas covered: In this review, we provide an overview of the continuum of care in GC, the molecular characterization of GC, targeted therapies currently under investigation and the role of immunotherapy. Expert commentary: Gastric cancer is a heterogeneous disease. A targeted approach based upon molecular phenotype holds promise for improving outcomes.